Importance of the Wheel Vertical Dynamics in the Squeal Noise Mechanism on a Scaled Test Bench. (2012) - Collette, C.
Abstract : This paper investigates the influence of the wheel vertical dynamics in the mechanism of squeal noise on a scaled test bench. To this purpose, sustained oscillations are first studied on a single degree of freedom oscillator, considering both a decreasing slope of the friction curve and a vertical excitation. Their relative importance to sustain the oscillations is discussed. Then, a mathematical model of a quarter scale test bench is developed in the frequency domain. Using this model, it is shown that the squeal noise resulting from the excitation of the bending modes of the wheel is sustained because these bending modes are associated with variations of the vertical contact force. Results are further confirmed by experiments conducted on a scaled test bench.